An analysis of adult non-neoplastic nephrectomies at a tertiary care centre in Mumbai - Gwendolyn Fernandes; Gwendolyn Phadnis (International Journal of Medical Research and Review, 2017)
Introduction: Nephrectomies are an integral part of urological practice and a wide range of renal diseases are seen on histopathological examination of non-neoplastic nephrectomy specimens.Objective: The objective of this study was to assess the incidence, clinical presentation and the histological spectrum of various non-neoplastic renal diseases detected in nephrectomy specimens at our institute and to compare our observations with the conventional patterns seen.Material and Methods: This is a retrospective 6 year study of adult non-neoplastic nephrectomies (ANNN) conducted in a tertiary care centre in Mumbai and includes 359 cases from January 2009 to December 2015. The paraffin blocks and slides were retrieved from our archives and analysed along with clinical features, radiological findings.Results: 359 ANNN specimens received over a 6 year period were studied. Most of the patients were in the sixth decade with a slight female preponderance. Flank pain was the commonest presenting symptom seen in 79.94% of cases. The most frequent surgical indication for ANNN was obstructive uropathy (47.08%) which includes calculus disease and PUJ obstruction followed by non-functioning kidney (42.06%). On histopathological examination, the most common gross pathology was acalculus hydronephrosis (40.67%) and the most frequent histopathological diagnosis was chronic pyelonephritis seen in 79.38% cases. Calculus obstructive uropathy amounted to 39.27% cases and acalculus obstructive uropathy amounted to 25.07% cases of chronic pyelonephritis.Conclusion: The most frequent surgical indication was obstructive uropathy and the most common histopathological diagnosis was chronic pyelonephritis. Calculus and acalculus obstructive uropathy amounted to almost 65% of the cases of chronic pyelonephritis.